Effect of medium-chain triglycerides on piglets in three farms in Selangor and Penang, Malaysia - Lim, Hiang Tee; Engku Ahmed, Engku Azahan; Ooi, Peck Toung; Ooi, Chee Hong (2010)
The aims of this study were to evaluate effect of medium-chain triglycerides (MCT) between treatment and control groups on growth performance, mortality rate and fecal coliform count in piglets. In addition, the effect of MCT on weaning body weight was evaluated. This study was separated into Phase I and Phase II. In phase I, 18 litters were selected from three farms in Selangor and Penang. Piglets in each litter was equally divided into control group and treatment group where only treatment group piglets were fed twice with 2 ml MCT on Day 1. Body weight was taken on day one, three, five and seven. Phase II involved 12 litters from a farm. The same procedure as in phase I was done, except the body weight was taken on day one, fourteen and twenty eight. MCT treatment group piglets were found to have higher growth performance and lower mortality rate thAn control group piglets. No difference in fecal coliform count was observed between treatment and control group. MCT showed more prominent effect on growth performance during weaning period of the piglets. In conclusion, MCT supplementation had positive effect on the growth performance of piglets as a result of increased body weight and average daily gain. Besides, MCT were able to reduce mortality in piglets in all the farms.